2022
DOI: 10.1186/s40168-022-01324-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of five freshwater cyanophages and reference-guided metagenomic data mining

Abstract: Background As important producers using photosynthesis on Earth, cyanobacteria contribute to the oxygenation of atmosphere and the primary production of biosphere. However, due to the eutrophication of urban waterbodies and global warming, uncontrollable growth of cyanobacteria usually leads to the seasonal outbreak of cyanobacterial blooms. Cyanophages, a group of viruses that specifically infect and lyse cyanobacteria, are considered as potential environment-friendly agents to control the har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Recently, we isolated a Myoviridae cyanophage termed Pam3 from Lake Chaohu in China, which specifically infects the host cyanobacteria Pseudanabaena mucicola ( 12 ). Genomic annotation indicated that, compared with phage T4, Pam3 harbors a much simpler baseplate composed of only six components gp19–gp24 encoded by the putative open reading frames ( Fig.…”
mentioning
confidence: 99%
“…Recently, we isolated a Myoviridae cyanophage termed Pam3 from Lake Chaohu in China, which specifically infects the host cyanobacteria Pseudanabaena mucicola ( 12 ). Genomic annotation indicated that, compared with phage T4, Pam3 harbors a much simpler baseplate composed of only six components gp19–gp24 encoded by the putative open reading frames ( Fig.…”
mentioning
confidence: 99%
“…The morphological characteristics of isolated phages were determined as previously described. 44 High titer phage sample (10 8 PFU/mL) was prepared after purification, placed on carbon-coated copper grids for 15 minutes for adsorption. After further drying, samples were stained with 2% uranyl acetate and examined in Tecnai G2 Spirit BioTWIN 120-kV transmission electron microscope (FEI Company, Hillsboro, USA) with magnification of 12000-16000 ×.…”
Section: Methodsmentioning
confidence: 99%
“…These genes can alter the physiology of an infected cyanobacterium, increasing the production of progeny phage [ 22 ]. At the beginning of 2022, the NCBI Genome database contained about 500 sequences of complete genomes of cyanophages, most of which were isolated from marine Synechococcus and Prochlorococcus (order Synechococcales), but there are only a few examples of isolated and published cyanophages infecting Oscillatoriales cyanobacteria [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and no Tychonema phages are described to date. However, some information about phage–host interactions can be recovered using the analysis of genomic CRISPR arrays [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%